Inspirative Story Through the Characteristics of Ester's Life: from an Outstanding to Queen - Janes Sinaga; Juita Sinambela; Kingston Pandiangan; Stepanus Pelawi; Beni Chandra Purba (PT FORMOSA CENDEKIA GLOBAL, 2022)
This life seems hopeless. Through Esther's story, it becomes an inspiration for everyone that His people have hope, have a future. The purpose of this research is so that every believer does not need to despair when the environment is not good, but remains enthusiastic, full of hope, full of submission to God, like what Esther did. This study uses a qualitative literature study method, by gathering useful theories to see gaps, conceptual support for the research topic. Esther is an inspirational figure in the lives of believers. The figure of Esther who lived without hope as an outcast and an orphan can be turned into a queen. All of this happened not because of luck but because of obedience, piety, humility and self-sacrifice which made him pleasing to everyone and especially to God